Students’ Listening Comprehension By Using English Breaking News - Tri Wahyuni Umagapit; Silvani Umar Ali; Hujaefa Hi. Muhamad; Samsudin Hi Adam (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The aim of this research is to determine listening comprehension using Breaking News English in third semester English students at Khairun University, Ternate. This research uses quantitative descriptive methods, this research involves 25 participants, research instruments use tests and documentation. The results obtained from the Listening Skills Test were that 16 students out of 25 students in the class were able to answer the questions very well. Research findings regarding listening comprehension showed that, of the 25 students, 16 (64%) were in the